Modelling stress-dependent single and multi-phase flows in fractured porous media based on an immersed-body method with mesh adaptivity. (November 2018) - Obeysekara, A.; Lei, Q.; Salinas, P.; Pavlidis, D.; Xiang, J.; Latham, J.-P.; Pain, C.C.
Abstract: This paper presents a novel approach for hydromechanical modelling of fractured rocks by linking a finite-discrete element solid model with a control volume-finite element fluid model based on an immersed-body approach. The adaptive meshing capability permits flow within/near fractures to be accurately captured by locally-refined mesh. The model is validated against analytical solutions for single-phase flow through a smooth/rough fracture and reported numerical solutions for multi-phase flow through intersecting fractures. Examples of modelling single- and multi-phase flows through fracture networks under in situ stresses are further presented, illustrating the important geomechanical effects on the hydrological behaviour of fractured porous media.